Fatal Basilar Aneurysm Rupture 6 Months Following Pipeline Flow Diversion Treatment - Stylianos Pikis; Tigran Petrosyan; Eftychios Archontakis; Georgios Arealis (Indian Journal of Neurosurgery)
Background Very delayed aneurysmal rupture represents a rare, poorly understood, catastrophic complication of intracranial aneurysm flow diversion (FD) treatment. Case Description A 48-year-old woman presented to the neurosurgical clinic for an elective admission 6-month post-FD treatment with a single pipeline embolization device (PED) treatment of a fusiform, large, midbasilar artery aneurysm. During her admission, the patient suffered a tonic-clonic seizure and collapsed. She was intubated and transferred for an urgent computed tomographic scan of the brain, which revealed subarachnoid hemorrhage and hydrocephalus. She was subsequently transferred to the operating room where an external ventricular drain was placed. Urgent diagnostic cerebral angiography revealed rupture of the previously treated aneurysm which was managed with deployment of a second PED and coil embolization of the right vertebral artery. Unfortunately, the patient succumbed to the disease 15 days later. Conclusion The pathophysiologic mechanism responsible for delayed aneurysmal rupture post-FD treatment remains to be defined and may involve an acute rise in intra-aneurysmal pressures in a partially thrombosed aneurysm, continued hemodynamic stress on the aneurysmal wall due to persistent blood inflow, and thrombus-induced inflammation-mediated degradation the aneurysmal wall. Further clinical and anatomical studies are necessary to define the mechanisms responsible for delayed aneurysm ruptures and identify appropriate preventive measures.